2011
DOI: 10.1002/asia.201000724
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Chemical Sensors Based on Pyrene Monomer–Excimer Dual Luminescence

Abstract: The past ten years have seen a spectacular development of chemical sensors based on the monomer-excimer dual luminescence of aromatic systems, such as pyrene. Either in the form of integrated or multicomponent molecular devices these chemosensors have been attracting a high interest above all because of their unique ratiometric properties. This review will focus on the latter systems, which can be classified into two classes: Firstly, the assembly of receptor-effector conjugates is triggerred by the analyte of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
141
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 235 publications
(144 citation statements)
references
References 135 publications
1
141
0
2
Order By: Relevance
“…[43][44][45][46] Significant efforts have been devoted to develop this class of probes for a wide range of analytes, including metal ions, 43,47 inorganic and organic anions, 48,49 enzyme activities, 50 and nucleic acids. [51][52][53][54][55][56][57][58] A typical way to produce the ratiometric signal is by using double fluorescent dyes, in which techniques based on fluorescence resonance energy transfer (FRET) are widely used.…”
Section: Dna-binding Small Ligand For Ratiometricmentioning
confidence: 99%
See 1 more Smart Citation
“…[43][44][45][46] Significant efforts have been devoted to develop this class of probes for a wide range of analytes, including metal ions, 43,47 inorganic and organic anions, 48,49 enzyme activities, 50 and nucleic acids. [51][52][53][54][55][56][57][58] A typical way to produce the ratiometric signal is by using double fluorescent dyes, in which techniques based on fluorescence resonance energy transfer (FRET) are widely used.…”
Section: Dna-binding Small Ligand For Ratiometricmentioning
confidence: 99%
“…[51][52][53][54][55][56][57][58] A typical way to produce the ratiometric signal is by using double fluorescent dyes, in which techniques based on fluorescence resonance energy transfer (FRET) are widely used. [44][45][46] For example, for the analysis of singlenucleotide polymorphism (SNP) in genomic DNAs, twofluorophore labeled hybridization probes have been developed based on the FRET strategy, [51][52][53][54] where pairs of Alexa 488-Cy5, 51 6-carboxyfluorescein-coumarin, 52 carboxy-x-rhodamine-Cy3, 53 and Cy3-Cy5 54 molecules were utilized. Another major approach to produce the ratiometric signal is based on the formation of excimers, 51,[55][56][57][58] and ratiometric fluorescent detection of SNP has been demonstrated using pyrene- 51,55,56 or perylene bisimide 57 -modified hybridization probes, and bispyrene diamines.…”
Section: Dna-binding Small Ligand For Ratiometricmentioning
confidence: 99%
“…To date, only a few studies have reported that employed α-carbonyl substituted pyrene derivatives in sensing systems [20]. Especially, the metal chemosensors constructed by α-carbonyl substituted pyrene derivatives is rare [21]. Based on these above information, we explored the application of γ-oxo-1-pyrenebutyric acid (OPBA), with a carbonyl group substituted on the α-position of the pyrene chromophore, as a selective and sensitive fluorescent chemosensor specific for Pd 2+ detection.…”
Section: 접착 및 계면 제 14권 제 1호 2013년mentioning
confidence: 99%
“…There was no pyrene excimer emission in the 2 : 1 complex formed between OPBA and Pd 2+ which suggested that the two pyrene chromophores are in the divergent position [11][12][13][14][15][16][17][18][19][20][21].…”
Section: +mentioning
confidence: 99%
“…Photonic aspects of supramolecular systems can be applied for use in materials detection [17,[35][36][37][38][39]. Detection of particular chemical species accompanied by specific variations of fluorescence emission is a powerful method in analytical chemistry.…”
Section: Recognitionmentioning
confidence: 99%